A RAB3GAP1 SINE Insertion in Alaskan Huskies with Polyneuropathy, Ocular Abnormalities, and Neuronal Vacuolation (POANV) Resembling Human Warburg Micro Syndrome 1 (WARBM1). Issue 2 (1st February 2016) - Wiedmer, Michaela; Oevermann, Anna; Borer-Germann, Stephanie E; Gorgas, Daniela; Shelton, G Diane; Drögemüller, Michaela; Jagannathan, Vidhya; Henke, Diana; Leeb, Tosso
Abstract: We observed a hereditary phenotype in Alaskan Huskies that was characterized by polyneuropathy with ocular abnormalities and neuronal vacuolation (POANV). The affected dogs developed a progressive severe ataxia, which led to euthanasia between 8 and 16 months of age. The pedigrees were consistent with a monogenic autosomal recessive inheritance. We localized the causative genetic defect to a 4 Mb interval on chromosome 19 by a combined linkage and homozygosity mapping approach. Whole genome sequencing of one affected dog, an obligate carrier, and an unrelated control revealed a 218-bp SINE insertion into exon 7 of the RAB3GAP1 gene. The SINE insertion was perfectly associated with the disease phenotype in a cohort of 43 Alaskan Huskies, and it was absent from 541 control dogs of diverse other breeds. The SINE insertion induced aberrant splicing and led to a transcript with a greatly altered exon 7. RAB3GAP1 loss-of-function variants in humans cause Warburg Micro Syndrome 1 (WARBM1), which is characterized by additional developmental defects compared to canine POANV, whereas Rab3gap1 -deficient mice have a much milder phenotype than either humans or dogs. Thus, the RAB3GAP1 mutant Alaskan Huskies provide an interesting intermediate phenotype that may help to better understand the function of RAB3GAP1 in development. Furthermore, the identification of the presumed causative genetic variant will enable genetic testing to avoid the nonintentional breeding of affected dogs.